Integrating islamic values into mathematics student worksheets: Validity study on exponents and radicals - Hakim, Abdur Rahman; Ramadhanti, Oktarisa; Bijani, Hilda Ladan; Azmi, Memen Permata; Nufus, Hayatun (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2025)
Student worksheets are instructional materials designed to help learners grasp subject matter, foster interaction with teachers, and encourage active engagement in the learning process. In Islamic-based schools, the integration of religious values into instructional resources is essential to provide meaningful learning experiences that support both cognitive and moral development. However, existing mathematics worksheets often lack such integration. This study aims to design and validate mathematics worksheets on exponents and radicals that explicitly integrate Islamic values. The research employed a Research and Development (R&D) design using Plomp’s development model, which consists of preliminary research, prototyping, and evaluation. The study, however, was limited to the prototyping and validation stages. Validation was conducted by three expert validators. The results revealed that the worksheets achieved an overall overall validity score of 90,50% from subject matter experts and 95,62% from instructional design experts, both categorized as very valid. These findings demonstrate that the integration of Islamic values into mathematics worksheets not only meets academic and design standards but also provides a meaningful approach to teaching mathematics that aligns with the spiritual and moral objectives of Islamic-based education.